2000
DOI: 10.1046/j.1523-1747.2000.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vernix Caseosa: Water Content, Morphology, and Elemental Analysis

Abstract: Recent studies have prompted interest in the use of epidermal barrier creams as protective biofilms for very low birthweight preterm infants. The key to understanding the role of epidermal barrier films is an elucidation of their interaction with water and a basic knowledge of their composition. In this study, we investigated the morphologic properties and elemental composition of the naturally occurring biofilm, vernix caseosa. This biofilm is typically lacking in preterm infants and its production coincides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 30 publications
3
73
1
4
Order By: Relevance
“…Vernix caseosa is a viscous, whitish substance coating the fetal skin surface during the last trimester. Morphologically, Agorastos et al (3) reported a cellular component of vernix, a finding confirmed and extended by our laboratory (4). Electron micrographs show the presence of fetal corneocytes surrounded by unstructured vernix lipid.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Vernix caseosa is a viscous, whitish substance coating the fetal skin surface during the last trimester. Morphologically, Agorastos et al (3) reported a cellular component of vernix, a finding confirmed and extended by our laboratory (4). Electron micrographs show the presence of fetal corneocytes surrounded by unstructured vernix lipid.…”
Section: Discussionsupporting
confidence: 87%
“…By composition, vernix is mainly composed of water (80%), lipid (10.3%), and protein (9.1%) (2). It consists of a lipid matrix containing detached corneocytes derived from possible remnants of the epitrichium, the differentiating fetal epidermis, and the pilosebaceous unit (3,4). Vernix lipid is, thus, composed of two types of lipid: sebaceous lipid and stratum corneum lipid (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Vernix loses its exogenous water slowly. 13 Application of vernix to adult volar forearm skin resulted in an increased capacity to bind exogenous water. 14 Vernix may also function to maintain skin hydration at birth and potentially facilitates formation of the acid mantle of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…3). Она состоит из секрета сальных желез, лануго и эпители-альных клеток, которые покрывают кожу плода [11]. В целом это комплекс представляет собой смесь, состоя-щую из 80% воды, 10% белка и 10% липидов, а именно плотно прилегающих друг к другу корнеоцитов, которые покрыты аморфным липидным матриксом [12,13].…”
Section: сыровидная смазка (Vernix Caseosa) до и после рожденияunclassified